Atypical symptoms and delayed diagnosis are more common in elderly patients with benign paroxysmal positional vertigo: a single-center study - Hongyan Li; Hongyan Li; Yanping Tong; Yan Wang; Yan Wang; Meimei Chen; Meimei Chen; Yu Cui; Yu Cui; Xiaolin Wu; Xiaolin Wu; Yi Ju; et al. (Frontiers in Neurology)
ObjectiveTo analyze the clinical characteristics of elderly patients with benign paroxysmal positional vertigo (BPPV), to provide a basis for the accurate diagnosis of elderly BPPV patients.MethodsA retrospective case-control study was conducted to evaluate the clinical data of 12,282 patients diagnosed with BPPV who received treatment at the Vertigo Clinical Diagnosis and Treatment Research Center of Beijing Tiantan Hospital, affiliated with Capital Medical University, between January 2020 and June 2024. Patients were categorized into an elderly group (≥65 years old) and a young-to-middle-aged group (<65 years old). Risk factors, clinical manifestations, and the interval from symptom onset to diagnosis were systematically compared and analyzed.ResultsThe mean age of elderly BPPV patients was 71.2 ± 5.4 years, with a male-to-female ratio of approximately 1:2. The posterior semicircular canal was the most commonly affected site (62.3%) in elderly patients, and the incidence of horizontal semicircular canal canalolithiasis was higher in the elderly group compared to the young-to-middle-aged group (16.2% vs. 13.6%, p < 0.001). The prevalence of arteriosclerosis-related risk factors (including hypertension, diabetes, hyperlipidemia, and coronary heart disease) was significantly higher (p < 0.001). Elderly patients with BPPV were more likely to experience atypical symptom (40.5% vs. 35.5%, p < 0.001), isolated vestibular symptom episodes lasting more than 1 min (23.1% vs. 21.4%, p = 0.039), and symptoms accompanied by tinnitus (21.0% vs. 18.8%, p = 0.004) and hearing loss (12.7% vs. 8.6%, p < 0.001). The proportion of elderly patients whose vertigo was triggered by typical head or body position changes was significantly lower than that in the younger group (35.3% vs. 39.7%, p < 0.001). Additionally, the time from symptom onset to diagnosis was positively correlated with age (r = 0.122, p < 0.001), and a significantly higher proportion of elderly patients experienced a diagnostic delay exceeding 14 days (35.4% vs. 28.4%, p < 0.001).ConclusionElderly patients with BPPV are more likely to present with atypical symptoms, fewer episodes of position-induced vertigo, and a longer symptom duration. Delayed diagnosis is more prevalent among elderly patients.